Anemonefish depletion reduces survival, growth, reproduction and fishery productivity of mutualistic anemone–anemonefish colonies - Frisch, A.; Rizzari, J.; Munkres, K.; Hobbs, Jean-Paul (2016)
Intimate knowledge of both partners in a mutualism is necessary to understand the ecology and evolution of each partner, and to manage human impacts that asymmetrically affect one of the partners. Although anemonefishes and their host anemones are iconic mutualists and widely sought by ornamental fisheries, the degree to which anemones depend on anemonefishes, and thus the colony-level effects of collecting anemonefishes, is not well understood. We tracked the size and abundance of anemone Entacmaea quadricolor and anemonefish Amphiprion melanopus colonies for 3 yr after none, some, or all of the resident anemonefish were experimentally removed. Total and partial removal of anemonefish had rapid and sustained negative effects on growth, reproduction and survival of anemones, as well as cascading effects on recruitment and productivity of anemonefish in the remaining colony. As predicted, total removal of anemonefish caused acute declines in size and abundance of anemones, although most anemone colonies (76 %) slowly resumed growth and reproduction after the arrival of anemonefish recruits, which subsequently grew and defended the hosts. Partial removal of anemonefish had similar but typically less severe effects on anemones. Remarkably, the colony-level effects on anemones and anemonefish were proportional to the size and number of anemonefish that were experimentally removed. In particular, anemone survival and anemonefish productivity were highest when one or more adult anemonefish remained in the colony, suggesting that adult fish not only enhanced the protection of anemones, but also increased the recruitment and/or survival of conspecifics. We conclude that the relationship between E. quadricolor and A. melanopus is not only obligate, but also demographically rigid and easily perturbed by anemonefish fisheries. Clearly, these two species must be managed together as a unit and with utmost precaution. To this end, we propose several tangible management actions that will help to minimize fishing effects.